Fenomena Self-harm: Studi Prevalensi pada Mahasiswa Fakultas Kedokteran Universitas Sriwijaya - Syarifah Aini; Patrick Chang; Diyaz Syauki Ikhsan; Bintang Arroyantri Prananjaya; Puji Rizki Suryani; Lathifah Nudhar (Malahayati Nursing Journal, 2026)
ABSTRACT Self-harm is the deliberate act of injuring oneself without suicidal intent and is commonly regarded as a maladaptive coping strategy for managing emotional distress. Medical students are particularly vulnerable because of the intense academic demands and psychological pressures associated with medical training. However, evidence regarding the prevalence of self-harm among Indonesian medical students remains limited. This study aimed to determine the prevalence of self-harm among undergraduate medical students at the Faculty of Medicine, Universitas Sriwijaya. A descriptive cross-sectional study was conducted between May and June 2021 using an online survey with the Self-Harm Behavior Questionnaire (SHBQ). A total of 187 preclinical medical students from the 2017–2019 cohorts participated, with most respondents coming from the 2017 cohort (71.7%). The findings revealed that 26 students (13.9%) had engaged in self-harm, comprising 18 students (9.6%) from the 2017 cohort, 4 students (2.1%) from the 2018 cohort, and 4 students (2.1%) from the 2019 cohort. The highest prevalence was observed among senior students, suggesting that cumulative academic responsibilities and prolonged exposure to educational stress may increase the likelihood of maladaptive coping behaviors. Self-harm was frequently reported as a means of regulating overwhelming negative emotions, expressing anger, or self-punishment. The prevalence identified in this study exceeded that reported among medical students in the United States (9.4%), which may partly reflect the anonymous nature of the survey that encouraged more candid responses. These findings highlight the need for early identification, routine mental health screening, and comprehensive psychological support programs within medical education. Keywords: Self-Harm, Self-Harm Behavior Questionnaire (SHBQ), Medical Students, Sriwijaya University.  ABSTRAK Self-harm merupakan perilaku melukai diri sendiri secara sengaja tanpa adanya niat untuk mengakhiri hidup dan sering muncul sebagai respons terhadap tekanan emosional. Mahasiswa kedokteran termasuk kelompok yang rentan mengalami self-harm karena menghadapi tuntutan akademik yang tinggi, sehingga prevalensinya di Indonesia penting untuk diketahui. Penelitian ini bertujuan menentukan prevalensi self-harm pada mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sriwijaya. Penelitian menggunakan desain deskriptif cross-sectional yang dilakukan secara daring pada mahasiswa preklinik angkatan 2017–2019 selama Mei–Juni 2021 menggunakan instrumen Self-Harm Behavior Questionnaire (SHBQ). Sebanyak 187 mahasiswa berpartisipasi, dengan mayoritas berasal dari angkatan 2017 (71,7%). Hasil penelitian menunjukkan prevalensi self-harm sebesar 13,9% (26 mahasiswa), terdiri atas 18 mahasiswa angkatan 2017 (9,6%), 4 mahasiswa angkatan 2018 (2,1%), dan 4 mahasiswa angkatan 2019 (2,1%). Proporsi terbesar ditemukan pada mahasiswa tahun akhir, yang bersesuaian dengan meningkatnya tuntutan akademik, tanggung jawab, serta akumulasi stres selama pendidikan kedokteran. Self-harm umumnya digunakan sebagai mekanisme koping maladaptif untuk meredakan emosi negatif, mengekspresikan kemarahan, atau menghukum diri sendiri. Prevalensi yang didapat pada penelitian ini lebih tinggi dibandingkan penelitian di Amerika Serikat (9,4%), kemungkinan dipengaruhi oleh penggunaan survey bersifat anonim sehingga responden lebih terbuka dalam melaporkan perilakunya. Temuan ini menunjukkan bahwa self-harm merupakan masalah kesehatan mental yang memerlukan perhatian serius, sehingga diperlukan upaya deteksi dini, skrining rutin, serta intervensi psikologis yang komprehensif di lingkungan pendidikan kedokteran. Kata Kunci: Self-Harm, Self-Harm Behavior Questionnaire (SHBQ), Mahasiswa Kedokteran, Universitas Sriwijaya.